К вопросу о дате основания Судака - Джанов, А.В.; Майко, В.В.; Фарбей, Ф.A. (Археологический альманах, 2012)
Basic sources in which Sugdeya is mentioned since the end of VII v. are in-process considered. Main attention is spared to history of discovery, study and publication of the unique writing source direct-coupled with history of Sugdeya – Sudak Sinaksar. Analyzed its notes which telling about the legendary date of city foundation. Unique possibility to confirm or refute the dating there are archaeological researches of ancient settlement of medieval Sugdeya. Fortification buildings, laying foundations of the Genoese and Byzantine buildings, which on a build technique and material very remind build receptions, used in the epoch of late antiquity, are shortly considered. The dating of these areas of fortification buildings by the archaeological way is not succeeded while. However during researches quite often were discovered artifacts, belong to time of legendary foundation of Sugdeya.